2021
DOI: 10.3390/jof7121074
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity and Composition of the Continental Solar Saltern in Añana Salt Valley (Spain)

Abstract: The Añana Salt Valley in Spain is an active continental solar saltern formed 220 million years ago. To date, no fungal genomic studies of continental salterns have been published, although DNA metabarcoding has recently expanded researchers’ ability to study microbial community structures. Accordingly, the aim of this present study was to evaluate fungal diversity using the internal transcribed spacer (ITS) metabarcoding at different locations along the saltern (springs, ponds, and groundwater) to describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…which reflects local geology and environmental conditions. Thus, extremophilic fungi have been isolated worldwide from saltern brines (1,4,23,54,134,140); from magnesium-rich bitterns (136); from the athalassohaline hypersaline waters of the Dead Sea, the Great Salt Lake, and the alkaline Wadi El Natrun in Egypt (5,85,133); from hypersaline industrial effluents in temperate and tropical climates (39,66,72); from cold hypersaline lakes in Antarctica; and from cryopegs in Siberian permafrost (37). As explained below, the survival of these fungi is supported by specialized adaptations at both genomic and phenotypic levels.…”
Section: Life In Hypersaline Water and Glacial Icementioning
confidence: 99%
See 1 more Smart Citation
“…which reflects local geology and environmental conditions. Thus, extremophilic fungi have been isolated worldwide from saltern brines (1,4,23,54,134,140); from magnesium-rich bitterns (136); from the athalassohaline hypersaline waters of the Dead Sea, the Great Salt Lake, and the alkaline Wadi El Natrun in Egypt (5,85,133); from hypersaline industrial effluents in temperate and tropical climates (39,66,72); from cold hypersaline lakes in Antarctica; and from cryopegs in Siberian permafrost (37). As explained below, the survival of these fungi is supported by specialized adaptations at both genomic and phenotypic levels.…”
Section: Life In Hypersaline Water and Glacial Icementioning
confidence: 99%
“…A few studies using culture-independent methods reported fungal DNA in glacial and hypersaline environments (4,29,93,134). These studies showed a considerable diversity of uncultivable fungi (e.g., Chytridiomycota) in glacial environments (8), but none so far in hypersaline environments.…”
Section: Future Researchmentioning
confidence: 99%
“…The most commonly isolated fungi from hypersaline lagoons and lakes belong to the families Aspergillaceae, Cladosporiaceae, Hypocreaceae, Pleosporaceae, Saccharomycetaceae, and Teratosphaeriaceae, with members of the Microascaceae family being less frequently recovered [15][16][17][18]. The Microascaceae family was established by Luttrell (1951) to accommodate the genus Microascus [19].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi need oxygen to decompose organic matter; thus, they are usually present in water, and aerated layers of soil in all geographical regions [ 1 , 2 ]. On the other hand, some genera and species, described as extremophiles, have been isolated also from samples of rocky and sandy deserts [ 3 , 4 ], salterns [ 5 , 6 ], and brine [ 7 ]. Extremophiles do not only survive but are also able to propagate in habitats with combined harsh living conditions, such as high salinity, low water activity, prolonged UV-radiation, drought, and high or low temperatures [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%